The Status of Land Cover in The Main Watershed (DAS) of Lombok Island and its Potential as Acause of Drought - Hidayatun Nufus; Taufik Fauzi; A. A. Ketut Sudarmawan; Suwardji; Mahrup (Jurnal Biologi Tropis, 2023)
Changes in land cover that occur from year to year continue to increase. Human activity, especially in the utilization of natural resources, especially forests for various purposes, resulted in an increase in open land as well as critical land. As a result, the upstream watershed area which originally had an important role for the hydrological cycle, gradually decreased its function and ability as a catchment area. The purpose of this writing is to find out the status of land cover in the main watershed of the Lombok island on the class of land cover that applies universally, and examine its potential as a cause of drought on the island of Lombok. This research was conducted using the descriptive method, through the following stages, namely (i) secondary data collection, (ii) data analysis and (iii) data interpretation. This research was conducted from March 2023 to June 2023. The research area covers the island of Lombok. The four main watersheds (DAS), namely Dodokan, Menange, Pustik and Jelateng. Data 12 Land cover, namely Evergreen/Deciduous needieleaf, Evergreen broadeaf tress, Deciduous brodeaf tres, Mixed/other tresses, Shurbs, Herbaceous vegetation, Cultivated and manged vegetation, Regularly flooded vegetation, Urban/built-up, Snow/ice, Barren, Open water downloaded from the wibe site earthenv.org. Altitude data is downloaded from the web site https://globalsolaratlas.info/map.